MODEL PENANAMAN KEDISIPLINAN ANAK USIA DINI PADA KELUARGA BURUH WANITA DI DESA BAKREJO KECAMATAN SUKOHARJO KABUPATEN SUKOHARJO - Gunairiyah, Meirina (BELIA: Early Childhood Education Papers, 2013)
Discipline needs to be invested since the child was a child as a way to help children to develop self- control. Educating children with discipline as the efforts of parents to guide children towards better behavior, so that children have the awareness and behave autonomously moral obedience comes from within the child. Moral values derived from the pattern of family life (father and mother) as the  ideal  model  for  imitation  and  identification  of  the  child's  behavior  and  self-identification through habituation. The purpose of this study was to: 1) determine the model of early childhood investment discipline, 2) determine differences  in perspective investment discipline to children between the mother and the father. The subjects in this study were kindergarten children aged 4-6 years,  parents  and  teachers  work  as  laborers.  Data  collection  techniques  used  observation, interview and documentation. Data analysis with data reduction, data display, and conclusion drawing  and  verification.  The  results  showed  that  the  model  of  early  childhood  investment discipline on women workers in the Village District Bakrejo Sukoharjo Sukoharjo includes models authoritarian, permissive and democratic. There is a difference of view between the child's investment discipline to mothers with fathers, mothers tend to use positive discipline approach while fathers tend to use negative discipline approach. It can be concluded that the environment in which a child grows and grew up going to affect the child's development process